The performance effect of feedback in a context of negative incentives: Evidence from a field experiment. (September 2018) - Lourenço, Sofia M.; Greenberg, Jeffrey O.; Littlefield, Melissa; Bates, David W.; Narayanan, V.G.
Abstract: We use a field experiment conducted in a North American hospital to study the performance effect of feedback when negative incentives are present. We analyze feedback effects on e-prescribing rates in a context in which the 181 physicians participating in our experiment have an e-prescribing target and a threat of termination for failing to reach that target. This research context is unique in its use of negative incentives, given that prior research shows that people react differently to positive versus negative incentives, but existing feedback-incentive studies commonly use only positive incentives. Our study finds that the effects of feedback differ according to the ex ante level of performance relative to the termination threshold. We find that low performers (those who are ex ante below the termination threshold) who receive feedback improve their e-prescribing rates less and later than low performers in the control group who do not receive direct information about their performance. These differences between the control and treatment groups are also present in a partition of medium performers who underestimate (or overestimate less) their performance, but are not present in either the partition of medium performers who overestimate more, high performers, or performers who exhibit feedback-seeking behavior.